Profil Pemberian Informasi ObatTerhadap Pasien dengan Resep Antidiabetes di Apotek Tangerang Selatan - Nelly Suryani; Yardi Saibi; Vidia Arlaini Anwar (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2020)
Providing drug information is very important to be conducted by pharmacists for patients who redeem drugs at their pharmacy, especially patients who fall into the priority category for counseling such as patients undergoing diabetes mellitus treatment. This study aimed to create a profile of drug / counseling information given by pharmacies in the South Tangerang area to patients with prescription of antidiabetic drugs. This was a descriptive cross sectional study. Data were collected by the simulation patient method played by 6 seniorundergraduate pharmacy students. Simple random sampling was used in taking 100 pharmacies from the population of pharmacies registered at the city health office. The scenario was in the form of a new prescription contained of 5 mg of glibenclamide without repetition which was intended for family member of the simulated patient. To identify officers who provided drug information, simulation patients asked confirmation questions to ascertain whether they were pharmacists or not. The results showed that as many as 88.65% of officers who provided drug information to simulated patients were non-pharmacists. The most commonly given information by the pharmacist was the frequency of drug use followed by the time of use and the purpose of use (indications) which were 100%, 90.91% and 54.55%, respectively. While the information items provided by non-pharmacists were the frequency of drug use followed by the intended use and time of use associated with meal times which were 83.72%, 61.63% and 40.70% respectively. It can be concluded that more the drug information provided to patients is carried out by unappropriate professionals namely pharmacists. Drug information delivered to patients both by pharmacists and by non-pharmacists is not maximally done. The role of pharmacists in providing drug information to DM patients needs to be increased